2015
DOI: 10.1089/ther.2015.0013
|View full text |Cite
|
Sign up to set email alerts
|

Seizures and Meperidine: Overstated and Underutilized

Abstract: Meperidine is used for pain control and treatment of shivering. Concerns about neurotoxicity, particularly seizures, have led to efforts limiting meperidine use. We reviewed the body of evidence linking meperidine to seizures. We searched PubMed for the terms meperidine, normeperidine, pethidine, and norpethidine; each was combined with the terms: seizure, epilepsy, epileptogenic, toxicity, overdose, seizure threshold, and convulsion. Articles were assessed for relevance. Semiologies were reviewed to ascertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…7 Pethidine usage has been associated with several undesirable side effects related to its metabolite norpethidine, including the propensity for epileptic activities. 8 Tramadol is an analgesic agent and its mechanism of action is through inhibition of the reuptake of 5hydroxytryptamine-3 (5-HT3) and norepinephrine. 9 These actions have been associated with thermoregulation and have led to its use as an antishivering agent.…”
Section: Introductionmentioning
confidence: 99%
“…7 Pethidine usage has been associated with several undesirable side effects related to its metabolite norpethidine, including the propensity for epileptic activities. 8 Tramadol is an analgesic agent and its mechanism of action is through inhibition of the reuptake of 5hydroxytryptamine-3 (5-HT3) and norepinephrine. 9 These actions have been associated with thermoregulation and have led to its use as an antishivering agent.…”
Section: Introductionmentioning
confidence: 99%
“…Schlick et al . [ 4 ] wrote an excellent review about meperidine-induced seizures. Based on their work and combined with the latest search results, we identified 35 clinically relevant studies of meperidine-associated seizures discussing a total of 52 patients.…”
mentioning
confidence: 99%
“…Schlick et al . [ 4 ] defined using meperidine 100 mg, 100–500 mg, >500 mg in adult in 24 h as low, medium, and high doses respectively. In their research, only two patients had reported seizure complications at low doses.…”
mentioning
confidence: 99%